Pyroptosis: a new insight into intestinal inflammation and cancer - Chao, Limin; Zhang, Wenjing; Feng, Yuchao; Gao, Pei; Ma, Jinyou (Frontiers in Immunology, 2024)
Pyroptosis is an innate immune response triggered by the activation of inflammasomes by various influencing factors, characterized by cell destruction. It impacts the immune system and cancer immunotherapy. In recent years, the roles of pyroptosis and inflammasomes in intestinal inflammation and cancer have been continuously confirmed. This article reviews the latest progress in pyroptosis mechanisms, new discoveries of inflammasomes, mutual regulation between inflammasomes, and their applications in intestinal diseases. Additionally, potential synergistic treatment mechanisms of intestinal diseases with pyroptosis are summarized, and challenges and future directions are discussed, providing new ideas for pyroptosis therapy.